2004
DOI: 10.1002/chin.200406112
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Insecticidal Activities of Novel 2,5‐Disubstituted 1,3,4‐Oxadiazoles.

Abstract: Syntheses and Insecticidal Activities of Novel 2,5-Disubstituted 1,3,4-Oxadiazoles. -A number of novel symmetrical [cf. (VI)] and unsymmetrical 2,5-disubstituted oxadiazoles [cf. (IV)] are synthesized and evaluated for their insecticidal activity. The oxadiazoles (IVd) and (IVe) exhibit significant activity. -(ZHENG, X.; LI*, Z.; WANG, Y.; CHEN, W.; HUANG, Q.; LIU, C.; SONG, G.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Such chemical compounds show anticancer and tyrosinase inhibitory activity [4]. Substituted 1,2,3-oxadiazoles have revealed antibacterial [5,6], antimycobacterial [7], antifungal [8,9], anti-inflammatory [10,11], analgesic [12], anticonvulsant [13,14] and insecticidal properties [15]. Oxadiazoles find use as fluorescent whiteners [16] and also act as muscle relaxants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such chemical compounds show anticancer and tyrosinase inhibitory activity [4]. Substituted 1,2,3-oxadiazoles have revealed antibacterial [5,6], antimycobacterial [7], antifungal [8,9], anti-inflammatory [10,11], analgesic [12], anticonvulsant [13,14] and insecticidal properties [15]. Oxadiazoles find use as fluorescent whiteners [16] and also act as muscle relaxants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of DGAT-1 increases insulin and leptin sensitivity. McCoull et al reported discovery and optimization of oxadiazole amide inhibitors, leading to the clinical candidate 16 (AZD3988). AZD3988 demonstrated excellent DGAT-1 potency (0.6 nM), good pharmacokinetics and preclinical in vivo efficacy.…”
Section: Antidiabetic Activitymentioning
confidence: 98%
“…Condensation of acylhydrazides (5) with aromatic or aliphatic acids in the presence of dehydrating agents such as sulfuric acid (H 2 SO 4 ), phosphorus oxychloride (POCl 3 ) and thionyl chloride (SOCl 2 ) is the most commonly used method to give symmetrical or asymmetrical 2,5-diaryl(alkyl)-1,3,4-oxadiazoles (7) (route b) [16]. These dehydrating reagents are highly toxic and corrosive.…”
Section: Preparation Of Oxadiazoles Derivativesmentioning
confidence: 99%
“…It has recently been shown that the 1,3,4-oxadiazole ring, one of the most important and well-known heterocyclic nuclei, exhibits a wide variety of pesticidal biological activities, including antibacterial, [7][8][9][10][11][12][13] antifungal, [14][15][16][17][18][19][20][21] antiviral, [21][22][23] insecticidal, [24][25][26][27] and herbicidal. 28,29 In addition, in 2005, Guimarães et al demonstrated that introduction of a 1,3,4-oxadiazole ring into target compounds could change their polarity, flexibility and metabolic stability, effectively enhancing their bioactivity.…”
Section: Introductionmentioning
confidence: 99%